Medical Environment of Traditional Market Quality in A Business Competition - Mohamad Tohari1, Khudzaifah Dimyati2, Absori Absori2, Nurhadiantomo2, Kelik Wardiono2, Wafda Vivid I (Institute of Medico-legal Publications Pvt Ltd, 2020)
There are two emerging markets in Indonesia, namely traditional markets and modern markets. Traditional market reform is one of the government’s programs to improve the performance of market traders. The existence of medicine environment aspects as the development of the quality of traditional markets is important to be discussed. The greater the health and medicine environmeny that occur shows a is a reflection of the level of public welfare. its development Traditional markets are beginning to be marginalized, this is due to the quality of commodities and un health environment that are not guaranteed.